Influência de soluções irrigadoras na resistência de união de um cimento resinoso auto adesivo à dentina - Oliveira, Bruna de [UNESP] (2014)
The aim of this study was to evaluate the microtensile bond strength between self-adhesive resin cement to dentin submitted to different surface treatments. Twenty-eight human molars were sectioned to exposure dentin and polished with #600-grit silicon paper. The samples were shared into 4 groups, according to the surface treatment (n=7): control, 2% chlorhexidine gluconate, 25% polyacrylic acid and 23ppm silver nanofiller. Blocks of TPH resin composite were luted to the dentin surface using RelyX U200 resin cement. The microtensile bond strength was measured in an Odeme Microtensile OM 100 machine, 24 hours after the bonding procedure. Data were submitted to Shapiro-Wilk normality test and means compared with Kruskal-Wallis test (α = 0.05). The highest value of microtensile bond strength was found for 25% polyacrilic acid (13.34 ± 6.36 MPa) without statistical difference from control group (9.76 ± 3.11 MPa). The silver nanofiller group (6.66 ± 3.56 MPa) did not also showed difference from control group. The lowest value was found for chlorhexidine gluconate (4.71 ± 2.19 Mpa). Based on the results, it can be concluded that the surface treatments can modify the microtensile bond strength of self-adhesive resin cement to dentin. The application of polyacrylic acid, as well as silver nanofiller, can be an useful clinical step to improve the mechanical bonding of the adhesive interface